Honeycomb-shaped biomass-derived porous carbon for removal of the heavy metal ions from domestic and industrial wastewaters - Bindhu, Devu; Sreekala, Chandrasekharannair Omanaamma; Jose, Rajan (Elsevier, 2025)
To address the water scarcity problems and heavy metal ions removal from domestic and industrial wastewaters, the present study demonstrates synthesis of honeycomb-structured carbon sourced from a non-edible biomass (coconut rachis) through carbonization and subsequent activation for porosity development. The carbon thus revealed a high surface area (1630 m2⸳g−1) and a well-developed porous structure, enhancing its adsorption capabilities, which when compacted within steel meshes, significantly removed (70–98 %) heavy metal ions like lead, nickel, chromium and copper from domestic wastewater. The detailed analysis using synthetic wastewater showed significant removal efficiencies in 30 min for lead, copper, phosphorus, and boron, with the maximum removal observed at higher adsorbent concentrations. The adsorption process followed the Dubinin–Radushkevich isotherm, suggesting that the process is physical adsorption. These findings highlight the potential of biosources for producing carbons of desirable morphologies for wastewater treatment.